Tumour necrosis factor-alpha gene polymorphisms in Iranian patients with biliary atresia - Nikou Fotouhi; Morteza Bonyadi; Zohreh Jahanafrooz; Nahid Ahmadian; Mahnaz Sadeghi-Shabestari; Saeid Aslanabadi; Robabeh Ghergherehchi; Milad Pormosavi; Mandana Rafeey (Wolters Kluwer Medknow Publications, 2014)
Background: Biliary atresia (BA) is a progressive inflammatory destructive process of the bile ducts. This study evaluated the relationship between single-nucleotide polymorphisms in the promoter region of tumour necrosis factor-alpha (TNF-α) gene and bilaiary atresia. Materials and Methods: Genomic deoxyribonucleic acid from 16 patients with established diagnosis of BA and 36 patients with INC was obtained. The genotypes of TNF-α-1031 (T/C) and TNF-α-308 (G/A) were determined using the restriction fragment length polymorphism-polymerase chain reaction and the results were analysis with proper statistic software. Results: The frequencies of T/T, T/C in TNF-α-1031 and G/G, G/A in TNF-α-308 were as same as control group. Moreover, we have same deduction for allele frequency and haplotypes analysis (T allele: 84.37%; G allele: 87.5%) in BA patients (T allele: 80.56%; G allele: 86.11%) in controls. In all cases variants of polymorphism did not affect the severity or incidence of BA disease. Conclusion: although no significant associations were found between BA and control groups, it seems meaningful that since the nature of BA is multi factorial. Next step will be considering a new target such as downstream modulation of the TNF-α pathway or other cytokines and chemokines which act directly/indirectly.